Over a million students use our free study notes to help them with their homework
Note that you can not take a positive base log of a negative number. log5(x2-5) - log5(x) = 2log5(2) => log5((x2-5)/x) = log5Answered by Milan L. • Maths tutor2898 Views
5
We will solve this question with the knowledge that dy/dx = u.(dv/dx) + v.(du/dx), where y=u.v We have y=e^x(3x+1)^2. First, we want to find u & v. By splitting the function, we have that u=e^x and v=...
We have 2tan(th) / (1 + tan^2(th)) = sin(2th)
We know that tan(A) = sin(A) / cos(A), and 1 + tan^2(A) = sec^2(A)
Therefore => (2sin(th) / cos(th)) / sec^2(th)
=> 2sin(th)*cos^2(...
We have 3^(2x+1) = 4^100
=> log(3^(2x+1)) = log(4^100)
=> (2x+1)log(3) = 100log(4)
←
434
435
436
437
438
→
Internet Safety
Payment Security
Cyber
Essentials